An assessment of leadership requirements for building strong libraries, strong library associations and strong societies (2023)
The chapter assesses leadership requirements for building strong libraries, library associations and societies in Nigeria, considering leadership traits, styles, leadership expectations of associations and what constitutes strong societies. A survey research design was adopted for the study in which university librarians were surveyed. Questionnaire was used to gather data. The data was analyzed using percentages and mean. It was found that preferred leadership traits and style for strong libraries, associations and societies are creativity, integrity, communication, passion, and vision that could be applied to transformational leadership. Library association leaders should demonstrate exemplary leadership with some elements of empathy, which translates to strong libraries and by extension strong societies where members possessing high literacy are empowered to contribute to the actualization of the mission and vision of the society. Recommendations are made on approach to development of the requisite leadership traits and styles necessary to build strong libraries, library associations and. ultimately, strong societies globally